NIWA news: going under ice to measure microbial mats - Vopel, K (NIWA, 2006)
The Dry Valley region of Southern Victoria Land, the largest icefree region of Antarctica, is one of the coldest and driest deserts in the world. There are numerous meltwater lakes in this region thanks to two regional features, the Transantarctic Mountain Range that blocks the flow of ice from the polar plateau and eliminates precipitation, and the very low mean air temperature (–15 to –30 ºC) that provides perennial ice cover, 3–6 m thick, to the lakes. Scientists have always been interested in the bacteria and microscopic algae inhabiting the lakes: they may offer insights into where and how life originated on earth, and where evidence of life – past or present – might occur on other planets on our solar system.